Once Again on Globalization, Human Rights and «Anthropological Optimism». Reflections on an Article by Miriam Fernández Calzada - Ya. G. Shemyakin (Ибероамериканские тетради)
There is an ever-increasing collision between two global processes that determine the way the modern world is, namely globalization and the «rebellion of exceptions», i.e., greater emphasis on particular features of people’s communities of various types, levels and scales, from small territorial associations to civilizations). Therefore, it is of paramount importance that we reconsider certain phenomena, which are vital both for the further development of people’s ideas about themselves and the world around them, and for determining the main directions of further activity of homo sapiens: globalization, human rights, and the manifestation of rationality in different civilizations. The article by M. Fernández Calzada is one of those very rare works that meet this demand. The author updates the legacy of F. de Vitoria and the Salamanca School, which is essential for providing a new outlook on the universal dimension of human history. That outlook is very different from the type of universalism whose content is determined by the formal rationality of Western origin and character, which embodied the «spirit of capitalism» (M. Weber). It is important to stress that the worldview of F. de Vitoria and his associates is «human-centric», yet at the same time, these Catholic thinkers completely rejected ultra-individualism based on the aforementioned type of ratio, which allows for direct parallels with the personalistic tradition of Russian philosophy. M. Fernández Calzada’s analysis of F. de Vitoria’s approach towards human rights helps to reconsider the issue, as we face the task of universalizing the concept of human rights and overcoming the tendency, which is still dominant in the global information space, towards limiting the interpretation of anthropological problems to the framework of the Western political and legal tradition. M. Fernández Calzada’s article points out that the Salamanca School and above all the works of F. de Vitoria represent a qualitatively different type of human rationality as compared to formal rationality. It is a rationality of values, which overcame the antagonism of faith and rationality and achieved their synergy. Finally, the «anthropological optimism» identified by the researcher as one of the defining qualities of the current she is studying, evokes direct associations with the «anthropological maximalism» of Eastern Orthodox Christianity, which allows us to conclude that certain currents in the Ibero-Catholic and Eastern Christian traditions are essentially close.